The Dynamics of the Relationship of the KGB of the Lithuanian SSR and the Central Committee of the Lithuanian Communist Party in 1954–1991 - Burinskaitė, Kristina (Genocidas ir rezistencija, 2011)
The relationship of the KGB of the Lithuanian SSR and the Central Committee of the Lithuanian Communist Party constitutes an important aspect for the analysis of the history of the operation of the Lithuanian KGB in Lithuania. This relationship is also significant when we attempt to answer the question of the extent to which local party authorities could influence the activity of the Lithuanian KGB and, accordingly, when we attempt to define the scope of powers and independence of the Lithuanian KGB.